PENGEMBANGAN NILAI-NILAI TRADISI MEUGANG DENGAN TEKNIK SELF INSTRUCTION UNTUK MENGURANGI KEJENUHAN PADA MAHASANTRI PONDOK PESANTREN AL-QUR’AN IBNU KATSIR 1 - Alhadi, Rizki; Nasruliyah Hikmatul Maghfiroh; Imaratul Ulwiyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
his research is driven by the phenomenon of learning burnout experienced by students at Ibnu Katsir 1, resulting from heavy academic workloads and monotonous routines. To address this issue, an innovative intervention is required that combines local wisdom with cognitive psychological techniques. This study aims to develop a model or guidebook that integrates the values of the Meugang tradition—such as togetherness, gratitude, joy, and a sense of kinship—through a self-instruction approach to reduce student learning burnout. The research method employed is Research and Development (R&D). The research procedures include the needs analysis phase, the development of products/materials based on Meugang values, expert validation, and limited field testing on research subjects. Data collection instruments consist of learning burnout scales, observations, and interviews. The results of this study are expected to demonstrate that the internalization of Meugang traditional values, combined with self-instruction techniques, is effective in helping students manage academic stress.